Impact of physical activity and dietary programme on metabolic syndrome risk factors in Saudi women - Al Hajri, Ahlam Saleh A (2018)
This thesis explores the impact of lifestyle factors on the development of metabolic syndrome (MS) in Saudi Arabian women. A survey of a snowball sample was used to recruit 258 female and explored factors influencing physical activity (PA) and food intake and their effects on BMI in women living in the KSA and the UK. Participants completed a self-reporting questionnaire relating to knowledge, attitudes, barriers and levels of PA, sedentary activity and eating habits. Excessive energy intake, physical inactivity and sedentary lifestyle were all prevalent in Saudi women, resulting in 80%, over the age of 35y, being overweight or obese. BMI was associated with both energy intake and PA, though the relationship with the former was stronger. The most common barriers to regular exercise were transportation and lack of time. Findings were generally similar between women living in Saudi Arabia and the UK. The efficacy of reducing energy intake, with or without increased PA, on risk factors associated with MS in overweight Saudi women was investigated in a pilot study. After a four-week program, incorporating dietary modification alone (D) or in combination with regular vigorous aerobic exercise (D+E), improvements were seen in body composition and a range of metabolic risk factors. Both groups lost weight, but, paradoxically, those in D lost significantly more than those in D+E (5.3 vs. 3.3%, p=0.016). Moreover, significant reductions were also found in blood pressure, plasma triacylglycerol, insulin, total and LDL cholesterol, with no significant differences between the two groups. Plasma glucose and HDL cholesterol remained unaltered. Overall, these changes led to a decline in the prevalence of MS from 20% to 5% and 21% to 7% for the D and D+E groups, respectively. Thus, reducing energy intake appears, at least in the short term, more important than increasing PA in reducing body weight and associated metabolic risk factors. These studies confirm that excessive dietary intake and physical inactivity both contribute to overweight and obesity in Saudi Arabian women. With appropriate support, it is possible to both reduce energy intake and increase PA, although, in the short -term, the former appears to be most important. It remains to be established whether longer-term improvements in PA would further improve metabolic health.